Teaching Competencies of Beginning Teachers participating in a Mentorship Project. Implications for University Professional Development - Herrera Torres, Lucía; Fernández Bartolomé, Ana María; Caballero Rodríguez, Katia; Trujillo Torres, Juan Manuel (Profesorado, Revista de Currículum y Formación del Profesorado, 2011)
The integration in the complex university structure of a beginning teacher is not a rapid or simple task. Teachers don´t know the organization and functioning of the university institution, the diversity of functions that they must realize and, along other many questions, though they are specialist in their subject, they cannot possess the teaching competencies that are necessary for design and implement education-learning processes of quality with their students. Mentorship Projects, where expert or mentor teachers advise and supervise, of voluntary and collaborative form, the process of induction to the teaching of beginning teachers suppose a very useful instrument to favour the mutual enrichment and the professional development in Higher Education. The aim of this study is to describe the process developed in the project "Coaching for teaching improvement in Higher Education. Mentorship Project of Beginning Teachers in the Faculty of Education and Humanities of Melilla ", financed by the Vice-Rector´s Office for Quality Assurance of the University of Granada. In addition, to analyze the level of development in a set of teaching competencies and the formative demand that presents a group of beginning teachers participant. The valuation of this project carry out by beginning teachers and mentor teachers is indicated also. The principal results reveal that, in spite of the fact that the beginning teachers indicate to possess an average level of development in the different teaching competencies raised, they show a high formative need in the design of teaching guide, the employment of diverse teaching methodology, and the skill to think and to research on the own teaching practice.Finally, different aspects that are of relevancy to facilitate the professional development of teachers in the university context are discussed.